2002
DOI: 10.1053/jhep.2002.35819
|View full text |Cite
|
Sign up to set email alerts
|

Terlipressin therapy with and without albumin for patients with hepatorenal syndrome: Results of a prospective, nonrandomized study

Abstract: Vasopressin analogues associated with albumin improve renal function in hepatorenal syndrome (HRS). The current study was aimed at assessing the efficacy of the treatment, predictive factors of response, recurrence of HRS, and survival after therapy. Twenty-one consecutive patients with HRS (16 with type 1 HRS, 5 with type 2 HRS) received terlipressin (0.5-2 mg/4 hours intravenously) until complete response was achieved (serum creatinine level < 1.5 mg/dL) or for 15 days; 13 patients received intravenous album… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
132
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 498 publications
(138 citation statements)
references
References 23 publications
5
132
0
1
Order By: Relevance
“…In three studies, the terlipressin arm was compared to a placebo arm [26, 27] or an ‘untreated arm’ [28] and in the two other studies terlipressin was compared to noradrenaline [29, 30]. In the five trials, all patients received intravenous albumin to optimize extracellular fluid volume and also because a nonrandomized study has shown that renal function improves more frequently in patients treated with terlipressin and intravenous albumin than in those treated with terlipressin alone [31]. However, there is no randomized trial of a vasopressor alone versus vasopressor plus albumin.…”
Section: Vasopressor Therapy For Hrsmentioning
confidence: 99%
See 1 more Smart Citation
“…In three studies, the terlipressin arm was compared to a placebo arm [26, 27] or an ‘untreated arm’ [28] and in the two other studies terlipressin was compared to noradrenaline [29, 30]. In the five trials, all patients received intravenous albumin to optimize extracellular fluid volume and also because a nonrandomized study has shown that renal function improves more frequently in patients treated with terlipressin and intravenous albumin than in those treated with terlipressin alone [31]. However, there is no randomized trial of a vasopressor alone versus vasopressor plus albumin.…”
Section: Vasopressor Therapy For Hrsmentioning
confidence: 99%
“…However, the effect of a dose of terlipressin may differ according to the degree of liver failure. The higher the Child-Pugh score, the greater the dose of terlipressin [31]. Interestingly, other studies used goal-directed terlipressin therapy [27,28,29]; terlipressin was initially given at a dose of 0.5 mg/4 h and increased in a stepwise fashion every 3 days to 1 and 2 mg/4 h if a significant reduction in serum creatinine (of at least 1 mg/dl (88 µmol/l)) was not obtained.…”
Section: Vasopressor Therapy For Hrsmentioning
confidence: 99%
“…Although Terlipressin has been more widely studied, the wide availability of Vasopression in countries where Terlipressin is unavailable has led to its use in treatment of HRS. A summary of studies using Vasopressin and its analogs can be found in Table 2 [7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…The half-life of terlipressin is 6 h whereas that of vasopressin is only 6 min [4]. Arteriolar vasoconstriction induced by lysine vasopressin is primarily mediated by nonselective stimulation of vascular smooth muscle V 1 receptors [1, 2, 4]. Because vasopressin (and its analogs) also activates V 2 receptors on endothelial cells causing a release of von Willebrand factor, it enhances platelet aggregation and therefore may increase the risk of thrombosis especially in cases of intense and/or prolonged vasoconstriction [1].…”
Section: Discussionmentioning
confidence: 99%
“…It has been largely used since the early 1990s mainly because of its prolonged duration of action, easy mode of administration and alleged low incidence of adverse effects [2, 3]. The major complications appear to result from tissue ischemia that may be severe and/or life threatening.…”
Section: Introductionmentioning
confidence: 99%